2012
DOI: 10.1111/j.1365-2702.2011.04053.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of written plus oral information vs. oral information alone on precolonoscopy anxiety

Abstract: There was a trend that information had a positive effect on patients' state anxiety. Future information provision studies may need to add more interactive methods appropriately and take patients' gender, educational level and coping style into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Bytzer and Lindeberg (2007) also reported the ineffectiveness of educations provided verbally and through video presentation in alleviating anxiety among gastroscopy candidates (16). Poursharifi et al (2013) and Luo (2013) also showed that written and verbal educations had no significant effect on endoscopy-related anxiety (5,13). All these findings are in line with our findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Bytzer and Lindeberg (2007) also reported the ineffectiveness of educations provided verbally and through video presentation in alleviating anxiety among gastroscopy candidates (16). Poursharifi et al (2013) and Luo (2013) also showed that written and verbal educations had no significant effect on endoscopy-related anxiety (5,13). All these findings are in line with our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies showed that there was no significant difference between the outcomes of written and verbal patient educations (5,13,24). However, Pehlivan et al (2011) reported the greater effectiveness of verbal education compared with written one (9).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This written educational material was especially critical to reduce the anxiety level in patients who underwent endoscopic biopsy and were more likely to have fear about a diagnosis of uncertain disease. 6 The method and timing of providing information to patients prior to endoscopic procedures are most important. If the information is offered to the patients in an inadequate way, the patients' anxiety may increase.…”
Section: Discussionmentioning
confidence: 99%
“…Educating patients about gastroscopy or colonoscopy in advance of the procedure, with written educational material or oral explanation, reduces patients' anxiety. 6 However, there is a lack of research about the effects on patients' anxiety of providing written educational material after biopsy during gastroscopy or colonoscopy.…”
Section: Introductionmentioning
confidence: 99%